The Communication Skills as Selection Criteria of Iranian National Table Tennis Coach: Sport Elites Perspectives - Tahereh Rahmati; Mehrzad Hamidi; Habib Honari (The Society of Aging and Physical Activity (SAPA), 2015)
The purpose of this study was to determine the prioritization and comparison of communication skills as a selection criterion of Iran's national table tennis coach from the sport elites perspectives. As this was a descriptive study, survey methodology was employed. The study population consisted of 100 table tennis sport elites of whom 80 subjects were randomly selected using the Morgan table. Questionnaires designed for the study consisted of 15 items. To determine the reliability of the questionnaire, Cronbach's alpha was used. McLean and Zakrajsk model was used in examining communication skills as a selection criterion of Iran's national table tennis coach. Results of this study indicate that there is no difference among the participants in prioritizing communication skills as a criterion (P>0.05).